2014
DOI: 10.1292/jvms.13-0434
|View full text |Cite
|
Sign up to set email alerts
|

CT and PET-CT of a Dog with Multiple Pulmonary Adenocarcinoma

Abstract: A 10-year-old, intact female Yorkshire terrier had multiple pulmonary nodules on thoracic radiography and ultrasonography with no lesions elsewhere. Computed tomography (CT) and positron emission tomography and computed tomography (PET-CT) using 18F-fluorodeoxyglucose (FDG) were performed to identify metastasis and undetected primary tumors. On CT examination, pulmonary nodules had a hypoattenuating center with thin peripheral enhancement, suggesting ischemic or necrotizing lesion. In PET-CT at 47 min after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…The tumour measured 10 × 8 cm, which is smaller than the one we found in the roe deer (15 × 20 cm). Even smaller, multiple tumours about 3 cm in diameter were identified in the case of adenocarcinoma in dog (4). Tumours can vary in sheep from small nodules to solid masses.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour measured 10 × 8 cm, which is smaller than the one we found in the roe deer (15 × 20 cm). Even smaller, multiple tumours about 3 cm in diameter were identified in the case of adenocarcinoma in dog (4). Tumours can vary in sheep from small nodules to solid masses.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,10 In veterinary medicine, 18 F-FDG-PET/CT has been shown to be an effective staging tool for patients with several different neoplasms, including lymphoma, mast cell tumour, mammary carcinoma, primary lung tumour, histiocytic sarcoma, Sertoli cell tumour and splenic hemangiosarcoma. 7,[11][12][13][14][15] Initial research has also shown that 18 F-FDG-PET/CT is effective for identifying both osseous and soft tissue lesions in dogs afflicted with appendicular osteosarcoma 4 and that the SUV max of the primary lesion is significantly associated with survival time. 10 However, the efficacy of 18 F-FDG-PET/CT has yet to be directly compared to other staging modalities.…”
mentioning
confidence: 99%
“…Znane są także warianty fizjologiczne oraz obraz charakterystyczny dla procesów łagodnych i artefaktów (17,43,47,57). W weterynarii została natomiast jedynie wstępnie opracowana ocena wartości SUV w celu różnicowania zmian łagodnych ze złośliwymi (5,29,34,36,39,43). Brak punktów odniesienia dla wartości SUV, a także stosowanie znaczników, które wykazują wysoki poziom fizjologicznej kumulacji, może dostarczać trudności interpretacyjnych (34).…”
unclassified
“…Badanie PET w weterynarii, podobnie jak u ludzi, w szczególności w połączeniu z tomografią komputerową czy rezonansem magnetycznym, pozwala na uzyskanie dokładnych informacji o anatomii i metabolizmie procesu nowotworowego, a także służy różnicowaniu guzów pierwotnych i przerzutów, wykryciu ognisk przerzutów, określeniu stopnia zaawansowania choroby, zaplanowaniu i monitorowaniu przebiegu dalszego leczenia (16,19,29,34,37,39,43,59). Badanie to znalazło uznanie w różnicowaniu zmian nowotworowych i zapalnych (51).…”
unclassified